First report of Meloidogyne javanica infecting Thymus vulgaris in the state of São Paulo, Brazil - Silva, Edicleide Macedo da; Koroiva, Ricardo; Ferreira, Rivanildo Júnior [UNESP]; do Nascimento, Daniel Dalvan [UNESP]; Peixoto Fernandes, João Pedro [UNESP]; Damasceno Neves, Benedito Charlles; Filho, Antonio Cesar de Araujo; Gomes, Rafaelle Fazzi; de Almeida, Nynyve Thaynar Brito; Paiva Negreiros, Andréia Mitsa; Vargas, Pablo Forlan [UNESP]; Bezerra, Laura Raissa Fagundes Costa; et al. (Elsevier, 2024)
Thymus vulgaris L. is found all over the world and is cultivated in several countries. It is considered an important medicinal plant with anti-inflammatory and aromatic properties. Its cultivation can suffer from infestation by numerous pathogens, which contributes to lower production. Thus, in 2020, a nematological survey in a vegetable growing area in Jaboticabal, São Paulo, Brazil, detected the presence of galls on the root, indicating that it was Meloidogyne spp. To identify the species, a sample with soil and roots was sent to the laboratory. After the analyzes performed, the species was identified as Meloidogyne javanica. This result was based on the morphological characteristics of the adults and the genetic identification. In the morphological part, the following characteristics were found: Perineal region of females low trapezoidal dorsal arch with two lines in laterals, while males have broader basal nodules with a non-raised labial disk, with the head region not separated from the body. Molecular confirmation was performed by genetic sequencing and sequence characterized amplified regions technique (SCAR). This is the first report of T. vulgaris as a host for M. javanica confirmed by Koch's postulate and several lines of evidence. Based on this report, farmers wishing to grow this vegetable should be aware of plants that are also hosts for this species.
Keywords: Detection; Molecular identification; Root-knot nematode; Thyme